Exploring Strategic Thinking Skills in Process Oriented Task in ESL Classroom - Najah, Osman; Hafizoah, Kassim (Elsevier Ltd., 2015)
English is used as the medium of instructions in most universities and colleges in Malaysia. Being a second language most students find it difficult to improve on the language specially to write report for process oriented task. Hence this paper draw on a research on using strategic thinking skills component to help improve in language learning and also process based oriented task. A researcher-developed taxonomy was design to address language problems in writing class of 56 students. Motivated Strategies Learning Questionnaire (MSLQ) adapted to current context was used to measure the learning strategies, motivation and learning awareness in the pre and post treatment to seek students’ interest and motivation in language learning. Result showed that the taxonomy did improved on both language learning and process oriented task.